Gestational diabetes: opportunities for improving maternal and child health. Issue 9 (September 2020) - Saravanan, Ponnusamy; ,; ,; ,; Magee, Laura A; Banerjee, Anita; Coleman, Matthew Anthony; Von Dadelszen, Peter; Denison, Fiona; Farmer, Andrew; Finer, Sarah; Fox-Rushby, Julia; et al.
Summary: Gestational diabetes, the most common medical disorder in pregnancy, is defined as glucose intolerance resulting in hyperglycaemia that begins or is first diagnosed in pregnancy. Gestational diabetes is associated with increased pregnancy complications and long-term metabolic risks for the woman and the offspring. However, the current diagnostic and management strategies recommended by national and international guidelines are mainly focused on short-term risks during pregnancy and delivery, except the Carpenter-Coustan criteria, which were based on the risk of future incidence of type 2 diabetes post-gestational diabetes. In this Personal View, first, we summarise the evidence for long-term risk in women with gestational diabetes and their offspring. Second, we suggest that a shift is needed in the thinking about gestational diabetes; moving from the perception of a short-term condition that confers increased risks of large babies to a potentially modifiable long-term condition that contributes to the growing burden of childhood obesity and cardiometabolic disorders in women and the future generation. Third, we propose how the current clinical practice might be improved. Finally, we outline and justify priorities for future research.